Probing Pocket Depth and Clinical Attachment Level between Non-Surgical and Surgical Periodontal Therapy in Chronic Periodontitis Patients: A Randomised Controlled Clinical Trial - Shah, Harish Kumar; Sharma, Shivalal; Goel, Khushboo; Shrestha, Sajeev; Niraula, Surya Raj (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Background: : Chronic periodontitis is one of the most common form of periodontal diseases which either require non-surgical periodontal therapy or open flap debridement-surgical therapy or both. To date, it is unclear as of how much changes occur after NSPT or OFD and which therapy provides the best outcome in chronic periodontitis having probing pocket depth ≥ 5-7 mm. Aim: The aim of this randomized controlled clinical trial was to evaluate the Probing Pocket Depth and Clinical Attachment Level between NSPT and OFD in chronic periodontitis patients. Materials and Methods: A total of 52 healthy patients with PPD ≥ 5-7 mm were included in the present study. Half of the patients assigned for the NSPT and half in the OFD group. The PPD and CAL were measured at baseline, three and six months. Independent sample t-test was used to compare the change in mean PPD and CAL between NSPT and OFD group at three and six months, respectively. Results: The difference in the mean decrease of PPD between NSPT and OFD group at three and six months were 0.15 mm (P<0.05) and 0.19 mm (P<0.05), respectively. The difference in the mean gain of CAL between NSPT and OFD group at three and six months were 0.03 mm (p>0.05) and 0.12 mm (P<0.05), respectively. Conclusion: Substantial improvement in periodontal status occurred with both the therapies, however, significantly higher decrease in PPD and gain in CAL were seen with surgical therapy.